ANALISIS SITUASI LINGKUNGAN DAN FORMULASI STRATEGI SEBAGAI TAHAPAN PERENCANAAN STRATEGIS PERSPEKTIF AKREDITASI PROGRAM STUDI - Ego Widoro (Politeknik Penerbangan Indonesia Curug, 2020)
Current condition in aviation require the strategic planning for program of study to be able to improve academic and non-academic quality to facing it by considering internal and external side. Within higher education strategic planning in terms of education remains three aspects that are Education, Research and Community Service are called Tridharma. Higher education strategic planning has been accommodated by accreditation form Badan Akreditasi Nasional Perguruan Tinggi (BAN-PT), so that improving academic and non-academic quality evidenced by rankings of accreditation. Environment analysis is first stage by using Delphi method to summarize the opinions from the experts about external condition to determine opportunity and threat. Internal condition analyzes by assessing using assessment of accreditation to determine strength and weakness. To find strategy in strategy formulation use matrix of opportunities, threats, strengths and weakness. Result of strategy formulation for each accreditation component in Program of Study Aircraft Engineering are: Organization vision, mission and stage time of achievement; improvements in budgeting, feedback and improving the graduates quality and create cooperation and dialogue with users, alumni participation, and study trace; improvement of academic qualifications, scientific activities and ratio of lecturers; number and qualifications of educational personnel; monitoring improvement of academic activities, curriculum development, academic atmosphere, quality of final project and safety culture; improved management, budget structure and budget allocations for the implementation of Tridharma; create scientific activity program, an increase in the interest of lecturer and other lecturer development activities. The next research is implementation and evaluation strategies.